The meritocracy or “responsibility elite”? An evangelical approach to the issue of social elites - Kopiec, Piotr (Annales. Etyka w Życiu Gospodarczym, 2019)
The notion of meritocracy is among the keywords used to describe the contemporary world. Increasingly, it has become a central concept of an order with globalization and the impact of free-market philosophy on society and culture as the main factors. The concept of meritocracy examines the nature of elites. On the one hand, meritocratic elites come from groups selected for their merits and competences; on the other hand, they avoid their responsibility towards society and culture. Amongst many counterproposals, it seems worthwhile to present the evangelical concept of elites embedded in evangelical social teaching. Evangelical theology introduces the idea of responsibility elites in its social discourse. According to evangelical theologians, in order to overcome the growing social, economic and cultural crisis of today, it might be necessary to rehabilitate the notion of the common good. Considered from a sociological and a theological standpoint, responsibility elites play a significant role in spreading the concept of the common good. The article presents theological guidelines for evangelical teachings on elites as well as evangelical proposals concerning the subject matter, collating them with a comprehensive assessment of meritocratic elites.